Early class III treatment with maxillary protraction-miniscrew-assisted rapid palatal expansion (MARPE) and mandibular miniplates - José Alfredo Facio-Umaña; Jorge Chaurand; Pedro IV Gonzalez-Luna (Elsevier, 2021)
Objective: Protaction of maxilla is usually the more commonly and less invasive treatment approach for skeletal Class III with a hypoplastic maxilla. The aim of this study was the comparison of the skeletal and dental effects of two treatment protocols for maxillary protaction: a)MARPE in combination with facemask (FM) b)MARPE and mandibular miniplates (MM). Patients: Thirteen patients (6 facemask, 7 mandibular miniplates) were investigated by means of pre- and posttreatment cephalograms and Conebeam Computer Tomographies (CBCTs). The two groups matched with regard to initial cephalometric and CBCTs values. The treatment objectives were to correct the transversal and antero-posterior maxillay deficiency. Results: Both groups showed a significant movement of A-point (FM group:+2.86 ± 0.94-p = 0.028; MM: 4.08 ± 0.64-p = 0.018). Also Both groups showed a significant change in ANB°, Wits appraisal and UL-ELine (mm). Upper and lower incisor inclination did not change significantly during treatment in both groups. Conclusions: Both treatments achieve comparable rates of maxillary protaction and expansion, without dentoalveolar side effects. However, it is important to consider age, the type of growth of the patient (high angle vs low angle) and the cooperation of patients and parents to one or another treatment. Consequently, the timing of treatment seems to be more important.